War of the worlds? : Pluralism vs. market liberalisation: the European regulation of the television broadcasting sector - Komorek, Ewa (Trinity College (Dublin, Ireland). School of Law, 2008)
This thesis makes the case for the European regulation of media concentration in the television broadcasting sector. Television broadcasting is currently undergoing substantial and rapid changes. The phenomena of digitalisation and the resulting technological convergence stimulate the minds of regulators in Europe and underlie the new Audiovisual Services Directive which is to replace the Television Without Frontiers Directive. There is even a trend to proclaim the death of television broadcasting understood as a traditional “point-to- multipoint” transmission of content, and the dawn of the era of Internet and interactive services. And yet, so far all studies and reports have shown that television remains the primary source of information for the majority of Europeans, and that not all consumers are willing to avail of the latest technological advances.
Keywords: Law, Ph.D.; Ph.D. Trinity College Dublin